2021
DOI: 10.3389/fcell.2021.657478
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Effects of Autophagy on NLRP3 Inflammasome in Inflammatory Nervous System Diseases

Abstract: Autophagy is a stable self-sustaining process in eukaryotic cells. In this process, pathogens, abnormal proteins, and organelles are encapsulated by a bilayer membrane to form autophagosomes, which are then transferred to lysosomes for degradation. Autophagy is involved in many physiological and pathological processes. Nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome, containing NLRP3, apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 116 publications
(131 reference statements)
0
37
0
Order By: Relevance
“…It participates in regulating inflammatory cascades in multiple diseases, in the meantime, shows a role in pyroptosis by affecting pore-forming protein gasdermin D (GSDMD). 32 , 33 ; The activated NLRP3 will promote pro-caspase-1 to transform into caspase-1 of hydrolysis activity, in turn activating several proinflammatory cytokines including IL-1β and IL-18. 34 GSDMD is a specific effector molecule involved in pore channel formation and the N-terminal fragment function is the key for the occurrence of pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It participates in regulating inflammatory cascades in multiple diseases, in the meantime, shows a role in pyroptosis by affecting pore-forming protein gasdermin D (GSDMD). 32 , 33 ; The activated NLRP3 will promote pro-caspase-1 to transform into caspase-1 of hydrolysis activity, in turn activating several proinflammatory cytokines including IL-1β and IL-18. 34 GSDMD is a specific effector molecule involved in pore channel formation and the N-terminal fragment function is the key for the occurrence of pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CTSB is an upstream activator of the NLRP3 inflammasome, promoting the release of IL-1β, and this effect can be inhibited by the CTSB inhibitor CA-074-Me5 (McHugh et al, 2019;Demirel et al, 2020). Additionally, CTSB inhibits autophagy by regulating the kinase ULK1 activity, and autophagy negatively regulates the activation of NLRP3 inflammasomes (Qi et al, 2016;Zhao et al, 2021). Similarly, recent evidence has illustrated that the use of autophagy inhibitors reversed the effect of betulinic acid, which reduces the activation of pyroptosis after SCI (Wu et al, 2021).…”
Section: Lysosomal Damagementioning
confidence: 99%
“…In recent years, increasing evidence has emphasized the importance of autophagy in limiting NLRP3 inflammasome-mediated excessive inflammation in various human diseases, such as neurodegenerative diseases, diabetes, and cardiovascular diseases [ [236] , [237] , [238] ]. In the past decade, many studies have proven that autophagy negatively regulates the activation of NLRP3 inflammasomes through various mechanisms.…”
Section: Targeting the Inhibition Of Nlrp3 Inflammasome-mediated Lung...mentioning
confidence: 99%